Understanding The Bully Verse in The Al-Qur’an with a Psychological Approach: Larangan Bullying Perspektif Al-Qur’an dengan Pendekatan Psikologis - Eko Seprianto (Takwil: Journal of Quran and Hadith Studies, 2022)
This research is motivated by negative actions, bad treatment, making fun of each other, or what is better known as bullying that occurs in society. Repeated bullying can have a psychological impact on a person. The purpose of this research is to understand the verses about the prohibition of the Bully in the al Quran and to find a solution with a psychological approach.This research uses the thematic method, namely discussing and analyzing the verses about the prohibition of Bully in the al Quran and understanding them with a psychological approach. The verses used as the object in this study are Surah al Hujurat verse 11, Surah al Baqarah verse 263 and Sura al A'raf verse 201. The results of this study are that due to bullying on a person's psychology can cause stress, headaches, depression. , mental disorders and even lead to loss of life. The solution to bullying according to the Koran is to increase piety to Allah, pray and get used to good words. Meanwhile, the psychological solution is to provide religious education, teach the values ​​of kindness, and carry out counseling and guidance and counseling activities.